Identifikasi dan Karakterisasi Isolat 23 Ducc Serta Kemampuannya dalam Memproduksi Enzim Inulinase - Wijanarka Wijanarka; K Endang; Hermin Hermin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
Inulinase has a capacity to convert inulin into fructose hence it could be used in high fructose syrup production. Inulinase is not readily available in Indonesian market. This enzyme could be obtained from thermotolerant yeast found in Dahlia variabilis. Therefore this study was conducted to identify inulinolytic yeast in D. variabilis. The results showed  that an inulinolytic yeast isolate 23 DUCC from D. variabilis tubers was found. The inulinolitic yeast produces inulinase (E.C.3.2.1.7). Based on the identification and determination, the isolate is known to be Kluyveromyces marxianus.  The best optimation condition for this yeast was as follows: concentration of carbon source (inulin) was 0.75%, pH was 5.5 and time of fermentation was 53 hours. In such condition K. marxianus  produced inulinase up to 0.6481 IU.